Valuation of the EQ-5D-5L with composite time trade-off for the German population – an exploratory study - Kristina Ludwig; J.-Matthias Graf von der Schulenburg; Wolfgang Greiner (Health and Quality of Life Outcomes, 2017)
Abstract Background The EuroQol Group has extended the severity levels of the EQ-5D from three to five (EQ-5D-5L). There are valuation studies worldwide planned in order to convert the EQ-5D-5L health states into a single preference-based summary score based on country-specific value sets of social health status preference valuations. The EuroQol Group developed an internationally standardised EQ-5D-5L valuation protocol. Based on the experiences of the first wave of valuation studies applying the protocol, a number of modifications to the implementation of composite time trade-off (cTTO) were proposed and tested in an exploratory study in Germany. Methods The aim of the study is to test the improved EQ-5D-5L valuation protocol 1.1 and the implementation of three modifications: (1) introduction of ranking task, (2) separating time trade-off (TTO) tasks for health states “Better Than Dead“(BTD)/“Worse Than Dead” (WTD), (3) allow for removal of problematic valuations from the cTTO data (the feedback module). Data were collected in computer assisted personal interviews with 200 members of the German general public. Results In comparison to the first wave of valuation studies a higher data quality can be observed in both study arms: increasing number of WTD valuations, reduced inconsistencies for health state 55555 as well as higher values for mild health states. Comparing both study arms, mean observed cTTO value for severity 6 is higher in the test arm. The proportion of inconsistent cTTO responses is lower in the test arm than in the control arm and is further reduced by the feedback module. The ranking task prolongs the interview without the desired effect. Conclusions Both study arms yielded higher data quality in comparison to the first wave of EQ-5D-5L valuation studies. The valuation protocol combined with an intensive interviewer training and close data monitoring showed a high feasibility and acceptability to the respondents of the general population as well as the interviewers in Germany. Based on the results of this study and other countries, the separation of TTO tasks for health states BTD/WTD and the feedback module will be implemented in the valuation study for the EQ-5D-5L for Germany.